THE IMPACT OF DA’WAH, PKS POLITICAL IDEOLOGY, AND SAMARA PROGRAM ON FAMILY RESILIENCE IN INDONESIA - Oniah, Siti; Majid, Zamakhsyari Abdul; Sutiono, Sutiono (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2025)
This study investigates the interconnections between the concept of da'wah (Islamic proselytization), the political ideology of Partai Keadilan Sejahtera (PKS), the Sakinah Mawaddah Wa Rahmah (SAMARA) family program, and their collective impact on family resilience in Indonesia. As political and social dynamics in Indonesia are increasingly shaped by Islamic values, particularly by PKS, this research explores how these values influence the social structure of family life and contribute to building a resilient society. Using a quantitative correlational approach, the study analyzes responses from 69 participants, mainly from the Women and Family Resilience Division of PKS Jawa Barat, through structured questionnaires. The results show significant positive relationships between the understanding of da’wah, PKS politics, and the SAMARA program with family resilience. These findings underscore the role of Islamic teachings and family-oriented political programs in fostering social stability and resilience. This research highlights the potential for integrated approaches combining political ideology and Islamic values to enhance the resilience of families in Indonesia, offering insights into the role of political parties in shaping societal wellbeing.